Cutaneous hypopigmentary disorders - An observational study - Kalegowda Deepadarshan; Bugude Gangadhar; Mallaiah Mallikarjun (Our Dermatology Online, 2016)
Background: Hypopigmented skin lesions is very common among people of all age groups. There are limited studies in India about evaluation of hypopigmented skin conditions. The aim of my study is to evaluate the different etiologies of cutaneous hypopigmentation. Aim: The present study was undertaken to find the relative incidence of the various disorders causing a hypopigmented lesion in a random sample of 200 cases and to study site, distribution and characteristics of the lesions. Methods: A random sample of 200 patients presenting with one or more hypopigmented lesions to the outpatient department of Dermatology, Venereology and Leprosy in KVG Medical College and Hospital, Sullia from December 2011 to January 2013 was studied. Detailed history including address and occupation with special reference to onset and duration, preceding skin conditions, exposure to chemicals, topical application and family history was taken. Various characteristics of the lesion like site, size, number, distribution, surface and sensation were studied. After this samples were taken for relevant investigations like complete hemogram, biopsy, slit skin smear, KOH mount and assessed for the causes of hypopigmented lesions. Results: In our study, most common cause with cutaneous hypopigmentation was pityriasis versicolor, seen in 52%, followed by post inflammatory hypopigmentation in 32%, pre vitiligo in 6.5%, Hansen's disease, idiopathic guttate hypomelanosis, nevus anemicus each in 2%, Woronoff's ring in 1.5% and miscellaneous conditions in 2% of the cases. Commonest age group affected was 21-30 years. Males (49%) and females (51%) were almost equally affected. Conclusion: The study concludes that various conditions comes under hypopigmentary disorders. More common in young adults. Most common scaly condition was pityriasis versicolor and non scaly condition was pre vitiligo. Proper counseling and ruling out Hansen's disease is required to alleviate the patient's anxiety. Background: Hypopigmented skin lesions is very common among people of all age groups. There are limited studies in India about evaluation of hypopigmented skin conditions. The aim of my study is to evaluate the different etiologies of cutaneous hypopigmentation. Aim: The present study was undertaken to find the relative incidence of the various disorders causing a hypopigmented lesion in a random sample of 200 cases and to study site, distribution and characteristics of the lesions. Methods: A random sample of 200 patients presenting with one or more hypopigmented lesions to the outpatient department of Dermatology, Venereology and Leprosy in KVG Medical College and Hospital, Sullia from December 2011 to January 2013 was studied. Detailed history including address and occupation with special reference to onset and duration, preceding skin conditions, exposure to chemicals, topical application and family history was taken. Various characteristics of the lesion like site, size, number, distribution, surface and sensation were studied. After this samples were taken for relevant investigations like complete hemogram, biopsy, slit skin smear, KOH mount and assessed for the causes of hypopigmented lesions. Results: In our study, most common cause with cutaneous hypopigmentation was pityriasis versicolor, seen in 52%, followed by post inflammatory hypopigmentation in 32%, pre vitiligo in 6.5%, Hansen's disease, idiopathic guttate hypomelanosis, nevus anemicus each in 2%, Woronoff's ring in 1.5% and miscellaneous conditions in 2% of the cases. Commonest age group affected was 21-30 years. Males (49%) and females (51%) were almost equally affected. Conclusion: The study concludes that various conditions comes under hypopigmentary disorders. More common in young adults. Most common scaly condition was pityriasis versicolor and non scaly condition was pre vitiligo. Proper counseling and ruling out Hansen's disease is required to alleviate the patient's anxiety.